2014
DOI: 10.3390/nu6010304
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Intake by Dutch 1- to 3-Year-Old Children at Childcare and at Home

Abstract: The goal of the current study was to assess dietary intake in a large sample (N = 1016) of Dutch toddlers (1–3 years old), both at childcare and at home. Dietary intake during two weekdays was recorded using an observation format applied by childcare staff for intake at childcare, and partially pre-coded dietary journals filled out by parents for intake at home. Children’s intake of energy, macronutrients and energy balance-related food groups (fruit, vegetables, sweet snacks, savoury snacks) were compared wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
68
5
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(81 citation statements)
references
References 30 publications
(61 reference statements)
6
68
5
2
Order By: Relevance
“…The Statistical Office of the Republic of Serbia has reported that Belgrade is the region with the highest percentage of day-care centre attendance and also the highest percentage of children who spend more than 9 h/d there, in comparison to other Serbian regions (42) . Although daycare centre attendance could serve as a protective factor against malnutrition (43,44) , a study conducted among Dutch toddlers (1-3 years old), both at childcare and at home, showed that children consumed more or less equal amounts of energy at home and childcare (45) . In Belgrade, we have quite the opposite situation.…”
Section: Discussionmentioning
confidence: 99%
“…The Statistical Office of the Republic of Serbia has reported that Belgrade is the region with the highest percentage of day-care centre attendance and also the highest percentage of children who spend more than 9 h/d there, in comparison to other Serbian regions (42) . Although daycare centre attendance could serve as a protective factor against malnutrition (43,44) , a study conducted among Dutch toddlers (1-3 years old), both at childcare and at home, showed that children consumed more or less equal amounts of energy at home and childcare (45) . In Belgrade, we have quite the opposite situation.…”
Section: Discussionmentioning
confidence: 99%
“…Little is known about the potential mechanisms linking child care with obesity, if such a relationship exists. The nutrition environment at child care may be an important mechanism to explore given recent studies in the US, the UK, and the Netherlands that highlight the nutritional inadequacy of foods and beverages commonly served to children in child care; specifically, meals and snacks lack sufficient fruits, vegetables, and whole grains and include excessive fats and sugars (Copeland, Benjamin Neelon, Howald, & Wosje, 2013; Frampton et al, 2014; Gubbels et al, 2014, 2015; Maalouf, Evers, Griffin, & Lyn, 2013; Neelon et al, 2015; Parker, LloydWilliams, Weston, Macklin, & McFadden, 2011). …”
Section: Introductionmentioning
confidence: 99%
“…Over 60% of children under the age of 5 regularly spend time under someone else’s care (Flynn et al, 2006; Johnson, 2005; Nicklas et al, 2001; Story, Kaphingst, & French, 2006). For children in full-time child care, approximately 50% of their daily dietary intake comes from meals and snacks eaten in this setting (Bollella et al, 1999; Gubbels, Raaijmakers, Gerards, & Kremers, 2014; Padget & Briley, 2005). …”
Section: Introductionmentioning
confidence: 99%